Wali Nikah Kedudukan Wali Nikah Anak Angkat Perempuan Yang Dicatat Sebagai Anak Kandung Dalam Kartu Keluarga Perspektif Mazhab Syafi'i - EVITA DESI SAFITRI; Anisatur Rofi'ah; Moh. Jeweherul Kalamiah (MASADIR: Jurnal Hukum Islam, 2025)
A marriage guardian (wali nikah), particularly for a virgin woman, serves as the legal representative who conducts the marriage contract on behalf of the bride and constitutes an essential pillar of marriage according to Islamic law. In the Madzhab Syafi'i, the validity of guardianship is based on a legitimate blood relationship (nasab), which places the biological father and paternal male relatives in the order of guardianship. However, in practice, some adopted daughters are administratively registered as biological children in the Family Card (Kartu Keluarga), creating legal uncertainty regarding the authority of the adoptive father to act as a marriage guardian. This study aims to examine the legal position of the marriage guardian for adopted daughters who are recorded as biological children in the Family Card from the perspective of Madzhab Syafi'i. This research employs a qualitative method using a library research approach. Data were collected through the examination of classical and contemporary Syafi'i jurisprudential literature, relevant legal regulations, and scholarly works concerning marriage guardianship and adoption. The findings reveal that administrative registration as a biological child does not alter the lineage status of an adopted child under Islamic law. Consequently, an adoptive father does not possess the legal authority to act as a marriage guardian for his adopted daughter. In cases where no legitimate lineage guardian is available, the authority of guardianship is transferred to the judge guardian (wali hakim). Therefore, the determination of a marriage guardian must be based on valid lineage rather than administrative records.